Differential Protein Profiling of Cerebrospinal Fluid in Piglets with Severe Meningoencephalitis Caused by Streptococcus suis Type 2 Compared to Controls - Liu, Hongtao; Jia, Li; Guo, Wenfei; Sun, Yingying; Zhu, Rining; Li, Shuguang; Qu, Guanggang; Jiang, Hexiang; Wang, Junjie; Gu, Jingmin; Sun, Changjiang; Feng, Xin; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
Streptococcus suis serotype 2 (SS2) is a zoonotic pathogen that can cause meningitis both in pigs and in human beings. However, the pathogenesis of central nervous system (CNS) infection caused by SS2 have not yet been elucidated. To find the key molecules in cerebrospinal fluid (CSF) needed for the pathogenesis, a SS2 meningoencephalitic pig model and a SS2 non-meningoencephalitic pig model were established in this study. CSF was collected from infected piglets, and protein profiling was performed with label-free proteomics technology. A total of 813 differential proteins, including 52 up-regulated proteins and 761 down-regulated proteins, were found in the CSF of meningoencephalitic pigs compared with both non-meningoencephalitic pigs and healthy pigs. These 813 differential proteins were clustered into three main categories, namely, cellular component, biological process, and molecular function by gene ontology (GO) analysis. The most enriched subclasses of differential proteins in each category were exosome (44.3%), energy pathway (25.0%) and catalytic activity (11.3%), respectively. The most enriched subclasses of upregulated proteins were extracellular (62.1%), protein metabolism (34.5%) and cysteine-type peptidase activity (6.9%), and of downregulated proteins were exosomes (45.0%), energy pathway (24.0%) and catalytic activity (9.4%). Then, the differential proteins were further investigated by using the KEGG database and were found to participate in 16 KEGGs. The most enriched KEGG was citrate cycle (56.6%), and some of these differential proteins are associated with brain diseases such as Huntington’s disease (18.6%), Parkinson’s disease (23.8%) and Alzheimer’s disease (17.6%). Sixteen of the 813 differential proteins, chosen randomly as examples, were further confirmed by enzyme-linked immunosorbent assay (ELISA) to support the proteomic data. To our knowledge, this is the first study to analyze the differential protein profiling of CSF between SS2 meningoencephalitic piglets and non-meningoencephalitic piglets by employing proteomic technology. The discovery and bioinformatics analysis of these differential proteins provides reference data not only for research on pathogenesis of SS2 CNS infection but also for diagnosis and drug therapy research. Key words: Streptococcus suis, Meningoencephalitis, Blood-CSF barrier, Cerebrospinal fluid, Proteomics